Electrochemical sensor, material for enhancing detection sensitivity of electrochemical sensor, construction method of electrochemical sensor, and application of electrochemical sensor in H2O2 concentration detection in cancer cell supernatant

Through the modified glass carbon electrode of palladium-palladium-cobalt boron single-atom mesoporous nanozyme and DDA-Cu electrode modified material, a high-sensitivity electrochemical sensor was constructed, which solved the problem of poor sensor stability and susceptibility to interference, and achieved the correctness of the The ultra-sensitive detection of H2O2 is suitable for the detection of H2O2 in cancer cells.

CN119125268APending Publication Date: 2024-12-13CHONGQING MEDICAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411384131.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing H2O2 electrochemical sensors have problems such as poor sensor stability, susceptible to interference from disturbing substances, and low linear range, making it difficult to achieve high sensitivity and real-time rapid detection.

Method used

Using palladium-palladium-cobalt boron single-atom mesoporous nanoenzyme and DDA-Cu electrode modified materials, an electrochemical sensor was constructed by modifying glass carbon electrodes, which improved catalytic activity and conductivity and enhanced the detection ability of H2O2.

Benefits of technology

It realizes ultra-sensitive and high specificity detection of H2O2, significantly improves detection accuracy, sensitivity and response speed, has good specificity, repeatability and stability, and is suitable for the detection of H2O2 in cancer cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119125268A_ABST
    Figure CN119125268A_ABST
Patent Text Reader

Abstract

The invention discloses an electrochemical sensor, a material for enhancing the detection sensitivity of the electrochemical sensor and a construction method of the electrochemical sensor in the technical field of electrochemical biosensors, and the material for enhancing the electrochemical detection sensitivity is selected from palladium-palladium cobalt boron monatomic mesoporous nano-enzyme or / and a DDA-Cu electrode modified material. The palladium-palladium cobalt boron monatomic mesoporous nano-enzyme is in the shape of a dendritic monodisperse sphere and has excellent peroxidase activity, and a DDA-Cu electrode modified material is an organic metal framework obtained after reaction of 1, 5-diamino-4, 8-dihydroxy-9, 10-diketone, copper acetate and absolute ethyl alcohol and has excellent conductivity. The electrochemical sensor constructed by combining the glassy carbon electrode modified by the DDA-Cu electrode modification material with the palladium-palladium cobalt boron monatomic mesoporous nano-enzyme has good electrochemical selectivity on H2O2, and can sensitively detect H2O2 released by cancer cells, which is of great significance to early discovery and diagnosis and treatment monitoring of cancers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrochemical biosensors, and in particular relates to an electrochemical sensor and a material and a construction method for enhancing the detection sensitivity thereof, and an application in detecting H2O2 concentration in cancer cell supernatant. Background Art

[0002] Hydrogen peroxide (H2O2) plays an important role in physiology. It is a relatively stable reactive oxygen species in biological tissues and a hub for the mutual conversion of reactive oxygen species. On the one hand, H2O2 can directly or indirectly oxidize biological macromolecules such as nucleic acids and proteins in cells and damage cell membranes, thereby accelerating cell aging and disintegration; on the other hand, H2O2 is also a key regulator in many oxidative stress reactions. As a very important substance involved in the metabolism of biological organisms, excessive accumulation of H2O2 can cause irreparable damage to cells and biological organisms. Studies have shown that cancer cells exhibit higher levels of H2O2 than normal cells. H2O2 is associated with cancer cell proliferation, apoptosis and metastasis, and excessive H2O2 enhances responsive drug release in tumor treatment. Therefore, the level of H2O2 has become an important parameter to determine whether cells are normal, and the detection of H2O2 can be used as a key influencing factor in early cancer treatment.

[0003] In recent years, many techniques including chemiluminescence, fluorescence analysis, spectrophotometry, gel electrophoresis, colorimetry and titration have been used to detect H2O2. However, optical techniques are limited by high cost, complex testing procedures, requirements for precision and bulky instruments, the need for trained personnel to operate, and interference from the sample matrix. At the same time, these techniques have low sensitivity or complex sample preparation procedures, which hinder the real-time and rapid measurement of H2O2. Compared with other technologies, biosensors including electrochemical sensors, aptamer-based biosensors and microfluidic devices are making great progress. Among them, electrochemical biosensors have the advantages of low cost, simple operation, high sensitivity and miniaturization, and have been widely used in the specific detection of various types of biomolecules. By adopting electrochemical technology as a potential solution to other expensive methods, many detection schemes have been reported. However, limited by the cumbersome biosensor construction scheme and the complex preparation method of bio-nanomaterials, the existing H2O2 electrochemical sensors still have problems such as poor sensor stability, susceptibility to interference from other interfering substances, and low linear range. Although electrochemical sensors and biosensors are considered to be effective solutions for detecting biomolecules, improving their stability, accuracy, selectivity, and reliability is always a primary requirement. Summary of the invention

[0004] The present invention aims to provide a material for enhancing the sensitivity of electrochemical detection and an ultra-sensitive, highly specific electrochemical sensor comprising the material, which will be of great significance for the real-time and sensitive detection of H2O2.

[0005] In the first aspect, a material for enhancing electrochemical detection sensitivity in the present invention is selected from palladium-palladium cobalt boron single-atom mesoporous nanozyme and / or DDA-Cu electrode modification material.

[0006] The palladium-palladium cobalt boron single-atom mesoporous nanozyme has a dendritic monodisperse spherical morphology and has excellent peroxidase activity. The preparation method thereof comprises the following steps:

[0007] S1. Add NH4F solution, H3BO3 solution, H2PdCl4 solution and Co(NO3)2 solution to the aqueous solution of dioctadecyl dimethyl ammonium chloride in sequence, and add NH3·H2O solution after incubation to fully stir the reaction;

[0008] S2, heating the solution prepared in S1, injecting the newly prepared borane dimethylamine complex solution, and stirring the reaction sufficiently to obtain PdCoB MNPs;

[0009] S3. The PdCoB MNPs synthesized in S2 were dissolved in N,N-dimethylformamide, and Na2PdCl4 solution was added. After stirring at low temperature for several hours, the mixture was repeatedly washed with anhydrous ethanol to obtain palladium-palladium cobalt boron single-atom mesoporous nanozymes, named Pd-PdCoBMNPs.

[0010] Furthermore, in the preparation method of Pd-PdCoB MNPs, the mass percentage of the NH3·H2O solution is 12wt.%, the concentration of the borane dimethylamine complex solution is 0.1M, and the concentration of the Na2PdCl4 solution is 10mM.

[0011] Furthermore, the DDA-Cu electrode modified material is a rod-shaped structure, which is an organic metal framework obtained by reacting 1,5-diamino-4,8-dihydroxy-9,10-anthraquinone, copper acetate and anhydrous ethanol, and is named DDA-Cu MOFs.

[0012] In the second aspect, the present invention also provides an electrochemical sensor, comprising a modified glassy carbon electrode and a signal label on the surface of the modified glassy carbon electrode; the signal label is the palladium-palladium cobalt boron single-atom mesoporous nanozyme, and the modified glassy carbon electrode is a glassy carbon electrode modified using the DDA-Cu electrode modification material.

[0013] In a third aspect, the method for constructing the electrochemical sensor described in the present application comprises the following steps:

[0014] S1. Preparation of modified glassy carbon electrode: dripping DDA-Cu electrode modification material solution on the surface of the purified glassy carbon electrode, and drying at 37°C to form a film;

[0015] S2. Add palladium-palladium cobalt boron single-atom mesoporous nanozyme solution dropwise onto the surface of the modified glassy carbon electrode and dry at 37° C. to obtain the electrochemical sensor.

[0016] Furthermore, the glassy carbon electrode (GCE) was polished with aluminum powder (Al2O3) slurry for 5 min to a mirror surface, and then ultrasonically cleaned with deionized water for 3 times, and dried with nitrogen for later use.

[0017] Fourthly, the electrochemical sensor described in the present application is used for detecting H2O2 content, and has an ultra-sensitive and highly specific detection effect.

[0018] The beneficial technical effects of the present invention are:

[0019] 1. The present invention creatively synthesizes a mesoporous nanozyme composite material characterized by isolated noble metal single atoms, namely palladium-palladium cobalt boron mesoporous nanozyme (Pd-PdCoB MNPs). The single atomization of noble metals can greatly reduce the material cost while maintaining the original catalytic activity. Single atoms are dispersed on a carrier with a large specific surface area, which can stabilize the single atoms, prevent their agglomeration, increase the surface free energy, and allow more atoms to participate in the actual catalytic reaction, thereby improving the single atom utilization and catalytic selectivity. Pd-PdCoB MNPs are mesoporous nanoparticles with three-dimensional interconnected nanochannels, which exhibit excellent catalytic activity due to their rich edge / corner sites, accessible mesoporous structure and high specific surface area. Pd-PdCoB MNPs have excellent peroxidase-like activity, can effectively catalyze H2O2 reduction reactions, and the signal of the catalytic hydrogen peroxide reaction can be sensitively captured by electrochemical methods, which is of great significance for the sensitive detection of hydrogen peroxide.

[0020] 2. Pd-PdCoB MNPs have the catalytic properties of natural enzymes, and also have the advantages of simple synthesis, adjustable catalytic activity and high stability.

[0021] 3. XPS analysis showed that the strong electronic interaction between the alloyed Pd, Co and B atoms changed the surface electronic structure of the Pd element, which was beneficial to enhance the catalytic activity of the Pd site. Enzyme kinetic analysis showed that Pd-PdCoB MNPs had better catalytic activity than horseradish peroxidase.

[0022] 4. The present invention further synthesized a DDA-Cu MOFs composite material with excellent conductivity. The material was characterized by transmission electron microscopy, showing that DDA-Cu MOFs was a rod-like structure of about 5 μm. After DDA-Cu MOFs was used to modify the glassy carbon electrode, an electrochemical sensor with high conductivity and catalytic activity was constructed.

[0023] 5. The DDA-Cu MOFs modified glassy carbon electrode provided by the present invention, combined with the electrochemical sensor constructed by the Pd-PdCoB MNPs provided by the present invention, has good electrochemical selectivity for H2O2 and is used for the detection of H2O2 in cancer cells. The results show that the electrochemical sensor can sensitively detect H2O2 released by cancer cells, which is of great significance for early detection and diagnosis and treatment monitoring of cancer.

[0024] 6. Clinical evaluation should show that the electrochemical sensor has good specificity, repeatability and stability.

[0025] 7. The present invention combines nanomaterial technology with biosensor technology, significantly improving the accuracy, sensitivity and response speed of electrochemical analysis technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Shown is a schematic diagram of the principle of detecting H2O2 according to the present invention.

[0027] Figure 2 Shown are morphological characterization images of the Pd-PdCoB single-atom mesoporous nanozyme of the present invention. (A) TEM image of Pd-PdCoBMNPs; (B) HRTEM image of Pd-PdCoB MNPs; (C) High-resolution TEM image of Pd-PdCoB MNPs; (D) AC-HAADF-STEM image of Pd-PdCoB MNPs; (E) HAADF-STEM image of Pd-PdCoB MNPs; (FI) STEM-EDS elemental analysis diagram of Pd-PdCoBMNPs.

[0028] Figure 3 The size distribution histogram and nitrogen adsorption-desorption isotherm of the Pd-PdCoB single-atom mesoporous nanozyme of the present invention are shown. (A) Pd-PdCoB MNPs size distribution histogram and (B) nitrogen adsorption-desorption isotherm of Pd-PdCoB MNPs.

[0029] Figure 4 Shown is the XPS spectrum of the Pd-PdCoB single-atom mesoporous nanozyme of the present invention. (A) Overall spectrum; (B) Pd3d; (C) Co 2p; (D) B 1s.

[0030] Figure 5Shown is the XRD image of the Pd-PdCoB single-atom mesoporous nanozyme of the present invention, with the XRD image of the PdCoB nanozyme used as a control.

[0031] Figure 6 The steady-state kinetic analysis of the Pd-PdCoB single-atom mesoporous nanozyme of the present invention is shown, with HRP and PdCoB as controls. (A) The curve of the substrate H2O2 concentration versus the HRP reaction rate, TMB concentration is 1mM; (B) The curve of the substrate TMB concentration versus the HRP reaction rate, H2O2 concentration is 10mM; (C) The curve of the substrate H2O2 concentration versus the PdCoB reaction rate, TMB concentration is 1mM; (D) The curve of the substrate TMB concentration versus the PdCoB reaction rate, H2O2 concentration is 10mM; (E) The curve of the substrate H2O2 concentration versus the Pd-PdCoB reaction rate, TMB concentration is 1mM; (F) The curve of the substrate TMB concentration versus the Pd-PdCoB reaction rate, H2O2 concentration is 10mM.

[0032] Figure 7 The catalytic kinetic analysis of the Pd-PdCoB single-atom mesoporous nanozyme of the present invention is shown, with PdCoB and HRP as controls. (A) UV spectra of Pd-PdCoB, PdCoB, and HRP; (B) Catalytic kinetic curves of Pd-PdCoB, PdCoB, and HRP; (C) Absorbance value curve at 650nm after the TMB substrate solution is catalyzed by Pd-PdCoB, PdCoB, and HRP with a concentration gradient.

[0033] Figure 8 The figure shows the changes in the catalytic ability of the Pd-PdCoB single-atom mesoporous nanozyme of the present invention under different pH and temperature conditions. (A) The absorbance value of the TMB substrate solution catalyzed by Pd-PdCoB at 650nm under different pH conditions; (B) The absorbance value of the TMB substrate solution catalyzed by Pd-PdCoB at 650nm under different temperature conditions.

[0034] Fig. 9 Shown are the EPR spectra of the Pd-PdCoB single-atom mesoporous nanozyme of the present invention in the presence / absence of H2O2, with PdCoB as a control. (A) EPR spectra of PdCoB and Pd-PdCoB in the absence of H2O2; (B) EPR spectra of PdCoB and Pd-PdCoB in the presence of H2O2.

[0035] Fig.10Shown is the morphology characterization of the electrode modified material DDA-Cu. (A) TEM image of DDA-Cu; (B) HRTEM image of DDA-Cu; (C) HAADF-STEM image of DDA-Cu; (DG) STEM-EDS elemental analysis of DDA-Cu.

[0036] Fig.11 EIS and CV characterizations of the electrochemical sensor are shown: bare GCE (a); bare GCE + Pd-PdCoB MNPs (b); bare GCE + DDA-Cu MOF (c); bare GCE + DDA-Cu MOF + Pd-PdCoB MNPs (d).

[0037] Fig.12 The electrochemical selectivity of Pd-PdCoB MNPs for H2O2 is shown. Bare GCE (a); bare GCE + Pd-PdCoBMNPs (b); bare GCE + DDA-Cu MOF (c); bare GCE + DDA-Cu MOF + Pd-PdCoB MNPs (d).

[0038] Fig.13 The feasibility of the electrochemical sensor for detecting H2O2 is demonstrated.

[0039] Fig.14 The optimized conditions of the electrochemical sensor are shown as follows: (A) Pd-PdCoB MNPs dilution optimization; (B) DDA-Cu MOFs dilution optimization; (C) detection electrolyte pH optimization.

[0040] Fig.15 The analytical performance of the electrochemical sensor is shown as follows: (A) DPV value of 0.01μM-8000μM H2O2 electrochemical detection; (B) Linear fitting of H2O2 concentration and current size.

[0041] Fig.16 Shown are the clinical application evaluations of the electrochemical sensor. (A) Specificity; (B) Repeatability; (C) Stability.

[0042] Fig.17 Shown is the DPV signal intensity of the electrochemical sensor detecting H2O2 in cancer cells.

[0043] In the figure, Pd-PdCoB is palladium-palladium cobalt boron single-atom mesoporous nanozyme (Pd-PdCoB MNPs, also known as Pd-PdCoB single-atom mesoporous nanozyme); in the figure, DDA-Cu is DDA-Cu electrode modified material (DDA-Cu MOFs). DETAILED DESCRIPTION

[0044] The following is further described in detail through specific implementation methods:

[0045] The main reagents used in the present invention are:

[0046] Borane dimethylamine complex (DMAB) was purchased from Acros Organics Chemical Company (Geel, Belgium);

[0047] Dioctadecyldimethylammonium chloride (DODAC) and boric acid (H3BO3) were purchased from Sangon Biotech Co., Ltd. (Shanghai, China);

[0048] Ammonium fluoride (NH4F) was purchased from General Reagent Company (Shanghai, China); Palladium (II) chloride (PdCl2) was purchased from Adamas Reagent Company (Shanghai, China);

[0049] Hydrogen peroxide (H2O2), ammonia solution (NH3·H2O), hydrochloric acid (HCl), and anhydrous ethanol were purchased from Chuandong Chemical Co., Ltd. (Chongqing, China);

[0050] 3,3,5,5-Tetramethylbenzidinedihydrochloride 16 H 20 N2.2HCl, TMB solution), 1,5-diamino-4,8-dihydroxyanthraquinone (DDA) was purchased from Aladdin Biochemical Technology Co., Ltd. (Shanghai, China);

[0051] Copper acetate (C4H6CuO4) was purchased from Shanghai Titan Technology Co., Ltd. (Shanghai, China);

[0052] Cobalt nitrate hexahydrate (Co(NO3)2.6H2O) and catalase were purchased from MacLean Biochemical Technology Co., Ltd. (Shanghai, China);

[0053] The ultrapure water required in the present invention is Millipore (Mill-Q) (Millipore, USA, ≥18MΩcm -1 )preparation.

[0054] The main instruments used in the present invention are:

[0055] All electrochemical signal detections were performed on a Chenhua CHI 660E electrochemical workstation (Shanghai, China) connected to a PC. The detection used a traditional three-electrode system: (1) DDA-Cu modified GCE (4 mm in diameter) as the working electrode; (2) a platinum wire electrode as the auxiliary electrode; and (3) a silver / AgCl electrode (immersed in a saturated KCl solution) as the reference electrode.

[0056] The morphological characterization of nanomaterials was performed using a Tecnai G2 F30 high-resolution transmission electron microscopy (HRTEM) produced by FEI, USA, with a point resolution of 0.20nm and an operating voltage of 200kV. The elemental analysis of nanocomposites was performed using an X-MAX energy dispersive spectrometer (EDS) from Oxford Instruments (London, UK). The specific surface area and pore size data of mesoporous nanozymes were collected using a TriStar II 3020 specific surface area analyzer (Brunauer-Emmett-Teller, BET) from McMerrittick (Georgia, USA). X-ray photoelectron spectroscopy (XPS) analysis was performed on a Thermo escalab250XI spectrometer (Massachusetts, USA), with a power of 150W, a beam spot of 650um, a voltage of 14.8KV, and a current of 1.6A. X-ray diffractometer (XRD) analysis was performed on a D8ADVANCE X-ray diffractometer from Bruker, Germany, with a tube current of 40 mA, a tube voltage of 40 kV, and a Cu target wavelength of 1.5406 angstroms. Electron paramagnetic resonance (EPR) was performed on an A300-10 / 12 electron paramagnetic spectrometer from Bruker, Germany.

[0057] Example 1: Preparation of palladium-palladium cobalt boron single-atom mesoporous nanozymes (Pd-PdCoB MNPs)

[0058] 120mg DODAC was dissolved in 40mL deionized water, magnetically stirred for 10min, ultrasonicated for 10min, and cycled twice to fully dissolve it. Subsequently, the pre-prepared NH4F solution (0.337M, 4mL), H3BO3 solution (0.101M, 4mL), H2PdCl4 solution (10mM, 2.56mL) and Co(NO3)2 solution (10mM, 2.134mL) were added to the above solution in sequence, and the magnetic beads were stirred for 5min to mix. Then, 1.6mL NH3·H2O solution (12wt%) was added to the solution, and the color of the solution was observed to change from light orange to light milky white. Next, the above solution was heated to 95℃ in an oil bath, and the magnetic beads were stirred for 20min. Finally, 4mL of freshly prepared DMAB solution (0.1M) was added to the solution, and after the solution changed from white to black, stirring was continued at 90℃ for 30min to obtain PdCoBMNPs. After cooling to room temperature, the precipitate was collected by centrifugation, washed four times with ethanol, and washed twice with deionized water. The precipitate was dispersed in 4 mL of deionized water to obtain a PdCoB MNPs solution for subsequent experiments. Take 1 ml of the prepared PdCoB MNPs solution, centrifuge to remove deionized water, redissolve in 5 ml of DMF, add the pre-prepared Na2PdCl4 solution (10 mM, 500 μl), and stir the magnetic beads under ice bath conditions for 2 hours. Finally, the reaction solution was repeatedly washed with anhydrous ethanol and deionized water, and the precipitate was collected to obtain Pd-PdCoB MNPs (where MNPs represents nanozymes).

[0059] Example 2: Morphological Characterization of Pd-PdCoB Single-Atom Mesoporous Nanozyme

[0060] The Pd-PdCoB MNPs synthesized in Example 1 were dispersed in 1 ml of deionized water to prepare a Pd-PdCoB MNPs solution. 500 μl of the Pd-PdCoB MNPs solution was taken, and the morphology of the nanocomposite material was photographed using a Tecnai G2 F30 high-resolution transmission electron microscope after silicon wafer preparation. Figure 2 A. Figure 3 As shown in A, the synthesized Pd-PdCoB MNPs are monodisperse spheres with an average particle size of about 90.51 nm. The nitrogen adsorption-desorption isotherm is shown in Figure 3 As shown in B, the BET specific surface area of ​​Pd-PdCoB MNPs is 48.74 m 2 / g, and the pore size is 19.00nm. High-resolution transmission electron microscopy images show that Pd-PdCoB MNPs form a fractal network similar to a dendritic molecular structure ( Figure 2 B. Figure 2E). The d-spacing of Pd-PdCoB MNPs was analyzed using Digital Micrograph software to be 0.232 nm, slightly larger than the d-spacing of pure Pd nanocrystals (0.225 nm), indicating that the B element can expand the Pd-Pd atomic spacing. Aberration-corrected high-angle annular dark-field scanning transmission electron microscopy (AC HAADF-STEM) measurements reliably identified single palladium atoms as the brightest contrast in the image, confirming the presence of atomically dispersed palladium atoms ( Figure 2 D) In ​​order to further verify the chemical composition of Pd-PdCoB MNPs, STEM-EDS element mapping analysis was performed. Figure 2 F- Figure 2 As shown in I, Pd, Co, and B elements are uniformly dispersed on the mesoporous nanospheres.

[0061] Example 3: XPS analysis of palladium-palladium cobalt boron single-atom mesoporous nanozyme

[0062] According to the method of Example 1, a sufficient amount of palladium-palladium cobalt boron single-atom mesoporous nanozyme was prepared, and the elements and chemical bonds of Pd-PdCoB MNPs were analyzed by X-ray photoelectron irradiation using a Thermoescal ab250XI spectrometer. Figure 4 A shows the total XPS spectrum of Pd-PdCoB MNPs, which contains Pd 3d, Co 2p and B1s peaks. 0 The binding energies of Figure 4 B), with a significant positive shift (1.2 eV) compared to Pd nanocrystals (340.3 and 335.0 eV, respectively), suggesting that the surface electronic structure of the Pd element in the Pd-PdCoB nanozyme is altered due to the strong electronic interaction between the alloyed Pd, Co, and B atoms. The Co 2p spectrum shows the abundance of Co 2+ and satellite peaks, Co in Co2p3 and Co2p1 2+ The binding energies of are 781.53 eV and 797.32 eV, respectively, which indicates that oxygen is easily adsorbed on Co atoms ( Figure 4 C). For metalloid B, the corresponding B1s spectrum also shows a predominantly oxidized B (B-Ox), which greatly suppresses the B 0 The generation of Figure 4 D). Co and B in the ternary alloy exhibit excellent oxygen adsorption properties, which is beneficial to enhancing the catalytic activity of the Pd active sites.

[0063] Example 4: XRD analysis of palladium-palladium cobalt boron single-atom mesoporous nanozyme

[0064] According to the method of Example 1, a sufficient amount of Pd-PdCoB MNPs was prepared, and X-ray photoelectron diffraction was performed using a D8 ADVANCE X-ray diffractometer to evaluate the crystal structure of Pd-PdCoB MNPs and compare it with PdCoB. Figure 5 As shown in Figure 2, a typical Pd peak (2Theta = 40.1°) was observed on PdCoB, which was attributed to the (111) plane of the Pd crystal. However, this peak was significantly reduced on Pd-PdCoB MNPs, suggesting the presence of a certain amount of Pd single atoms.

[0065] Example 5: Enzyme kinetics analysis of palladium-palladium cobalt boron single-atom mesoporous nanozyme

[0066] The present invention further explores the peroxidase activity of Pd-PdCoB MNPs, catalyzes TMB to produce a color reaction, and uses the absorbance value at 650nm as the observation value.

[0067] 1. Steady-state kinetic analysis

[0068] Synthesize a sufficient amount of Pd-PdCoB MNPs, PdCoB MNPs, centrifuge and dry the precipitate, weigh it, and dissolve it in deionized water to 0.5 mg / ml. Take an appropriate amount of HRP and dissolve it in deionized water to 0.0001 mg / ml. Prepare a sufficient amount of 0.2M, pH 5 acetic acid-sodium acetate buffer solution, hereinafter referred to as buffer. Construct a TMB color reaction system, 10μl enzyme, 20μl TMB solution, 20μl H2O2 solution, 150μl buffer solution, and the total reaction volume is 200μl. Take 10μl Pd-PdCoB MNPs and add 150μl buffer to a 96-well plate. When TMB is used as a substrate, add 10μl TMB solution and control its final concentration to be 0.5, 0.007813, 0.015625, 0.03125, 0.0625, 0.125, 0.25, and 0.5mM. Then add 20μl 100mM H2O2 solution, and repeat three times for each group. Place the ELISA plate in an ELISA reader and react at 37°C for 2min, and measure the absorbance at 652nm. Calculate the reaction rate according to the Lambert-Beer law. According to the Michaelis equation, the reaction rate is compared with the substrate concentration to draw the Michaelis equation curve, such as Figure 4As shown in A. Similarly, when H2O2 is used as a substrate, first add 20μl of 10mM TMB solution. Then add 20μl of H2O2 solution and control its final concentration to 0.125, 0.25, 0.5, 1, 1.5, 2, 2.5mM. Repeat three times for each group. Place the ELISA plate in an ELISA reader at 37°C for 2 minutes, and measure the absorbance at 652nm. Calculate the reaction rate based on the Lambert-Beer law. Based on the Michaelis-Menten equation, plot the reaction rate against the substrate concentration to form a Michaelis-Menten curve, as shown in Figure 1. Figure 4 B. The steady-state kinetic analysis method of PdCoB nanozyme and HRP is the same as above, and the Michaelis equation curve is shown in Figure 4 C, D, E, and F. The calculated maximum reaction rates (Vmax) and Michaelis constants (Km) of Pd-PdCoB MNPs, PdCoBMNPs, and HRP are shown in Table 1, where Pd-PdCoB MNPs has the largest Vmax and the smallest Km, indicating that it has the best catalytic activity.

[0069] Table 1. Kinetic parameters of Pd-PdCoB MNPs, PdCoB MNPs, and HRP

[0070]

[0071] 2. Catalytic kinetic analysis

[0072] Pd-PdCoB MNPs, PdCoB MNPs, 50 μl of HRP solution, 800 μl of supplementary reaction buffer, and then 100 μl of 10 mM TMB solution and 50 μl of 400 mM H2O2 solution were added to the test tube in sequence. The reaction mixture was placed in a light-proof water bath at 37°C for 2 minutes, and the colorimetric reaction was measured by the absorbance at 652 nm every 10 seconds for the next 300 seconds. The absorbance at 652 nm was plotted against the reaction time to obtain a reaction-time curve. The absorbance value was plotted against the enzyme concentration to compare the ability of the three enzyme substances to catalyze the TMB reaction. At the same time, the UV absorption spectra of the three enzyme substances were measured. This part of the analysis is as follows Figure 7 shown.

[0073] 3. Investigate the effects of temperature and pH on the TMB reaction catalyzed by Pd-PdCoB nanozymes

[0074] The reaction system was 1 ml, in which the TMB concentration was 10 mM, the H2O2 concentration was 400 mM, and the Pd-PdCoB MNPs concentration was 1.025 pM. The absorbance at 652 nm was measured at pH 3, 4, 5, 6, 7, 8, 9, and 10, respectively. The absorbance was repeated three times and the pH value was plotted as shown in the figure. Figure 8At the same time, the absorbance at 652 nm was measured at incubation temperatures of 20, 30, 40, 50, 60, 70, 80, and 90 °C, and repeated three times. The absorbance value was plotted against temperature as shown in Figure 8 As shown in B. In a relatively wide range of pH and temperature, Pd-PdCoB nanozyme maintains high catalytic activity.

[0075] 4. EPR analysis of Pd-PdCoB MNPs

[0076] Take appropriate amount of Pd-PdCoB MNPs and PdCoB MNPs, and measure the electron paramagnetic spectrum on A300-10 / 12 electron paramagnetic spectrometer in the presence or absence of H2O2. Fig. 9 As shown in the EPR spectra, in the absence of H2O2, neither PdCoB MNPs nor Pd-PdCoB MNPs produce hydroxyl radicals. However, in the presence of H2O2, a large amount of hydroxyl radicals can be observed, and Pd-PdCoB MNPs has a stronger ability to produce hydroxyl radicals, suggesting that it has better catalytic activity.

[0077] Example 6: Morphological Characterization of DDA-Cu Electrode Modified Materials (DDA-Cu MOFs)

[0078] In order to improve the detection performance of the electrochemical sensor, a metal organic framework (DDA-Cu MOFs) material with excellent conductive properties was synthesized for glassy carbon electrode modification. The synthesis method is as follows: 30 mg of DDA was added to 100 ml of ethanol and 400 ml of water to prepare solution A, and 22.2 mg of copper acetate was dissolved in a mixed solution of 100 ml of ethanol and 400 ml of water to prepare solution B. Solution A was ultrasonically treated for 30 minutes to ensure full dissolution. Solution A was stirred while solution B was added to solution A (about 2 drops per second). The mixed solution was then stirred at 90 ° C for 24 hours at normal pressure. After the reaction was completed, it was centrifuged at 9000 rpm and repeatedly centrifuged with ethanol and water until the supernatant was clear. The blue-black precipitate was collected and dissolved in 5 mL of deionized water to obtain a DDA-Cu MOFs solution for subsequent experiments.

[0079] Take 500 μl of the newly synthesized DDA-Cu MOFs solution, prepare the silicon wafer and use a Tecnai G2 F30 high-resolution transmission electron microscope to take the morphology of the nanomaterial. Fig.10 A. Fig.10 As shown in Figure B, the newly synthesized DDA-Cu is a rod-like structure with a length of about 5 μm. In order to further verify the chemical composition of DDA-Cu MOFs, STEM-EDS element mapping analysis was performed, such as Fig.10 C- Fig.10As shown in G, C, N, O, and Cu elements are evenly dispersed on the MOF material.

[0080] Example 8: EIS and CV Characterization of Electrochemical Sensors

[0081] The method for constructing an electrochemical sensor is as follows: the glassy carbon electrode (GCE) is polished with aluminum powder (Al2O3) slurry for 5 minutes to a mirror surface, then ultrasonically cleaned with deionized water for 3 times, and dried with nitrogen for subsequent modification. An appropriate amount of DDA-Cu MOFs solution is dropped on the treated GCE surface and dried at 37°C to form a film. DDA-Cu MOFs modifies the glassy carbon electrode and gives it excellent conductive properties. Subsequently, an appropriate amount of Pd-PdCoB MNPs solution is dropped on the modified glassy carbon electrode and dried at 37°C to successfully assemble the electrochemical sensor. In order to characterize the step-by-step preparation process of the modified electrode, electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV) were used for characterization. The measurement process was carried out in a solution containing 0.1M KCl and 5mM K3[Fe(CN)6] and K4[Fe(CN)6]. EIS can be used to verify the modification process and sensing interface characteristics of the prepared immunosensor. In EIS, the diameter of the semicircle represents the electron transfer resistance (Ret). EIS and CV measurements were performed on bare glassy carbon electrode, glassy carbon electrode modified with DDA-Cu MOFs, glassy carbon electrode incubated with Pd-PdCoB MNPs only, and electrochemical sensors incubated with Pd-PdCoB nanozymes on modified glassy carbon electrode. Fig.11 As shown, the EIS and CV results confirmed each other, suggesting the successful construction of the electrochemical sensor.

[0082] Example 9: Electrochemical selectivity of electrochemical sensor for H2O2

[0083] The electrochemical sensor was constructed according to Example 8, and its electrochemical selectivity for H2O2 was characterized by cyclic voltammetry (CV). The measurement process was carried out in a 0.1 M PBS solution with or without 5 mM H2O2. CV measurements were performed on the bare glassy carbon electrode; the glassy carbon electrode modified with DDA-CuMOFs; the glassy carbon electrode incubated with Pd-PdCoB MNPs only, and the electrochemical sensor incubated with Pd-PdCoB MNPs on the modified glassy carbon electrode. Fig.11 As shown, the electrochemical sensor incubated with Pd-PdCoBMNPs on the modified glassy carbon electrode had the best electrochemical response, suggesting its possibility for detecting H2O2.

[0084] Example 10: Feasibility of detecting H2O2 using electrochemical sensors

[0085] The electrochemical sensor was constructed according to Example 8, and its differential pulse voltammetry (DPV) response value was observed using an electrochemical workstation. A 0.1M PBS electrolyte without H2O2 was set as a control group, and a 0.1M PBS electrolyte containing 5mM H2O2 was set as a test group, and the DPV response values ​​of the electrochemical sensor in the two electrolytes were measured respectively. Fig.13 As shown in the figure, in the absence of H2O2, the DPV signal is very weak (curve a). When 5 mM H2O2 is added, the DPV signal increases significantly (curve b), which shows that the sensor is feasible for detecting H2O2.

[0086] Example 11: Optimization of electrochemical sensor detection conditions

[0087] In order to optimize the detection performance of the present invention, the experimental conditions were optimized. First, the dilution factor of the Pd-PdCoB mesoporous nanozyme was optimized. Fig.14 As shown in A, the electrochemical sensor has the best detection performance when Pd-PdCoB MNPs are diluted 4 times. Then, the dilution factor of DDA-Cu MOFs was optimized, as shown in Fig.14 As shown in B, when DDA-Cu MOFs was diluted 8 times, the electrochemical sensor had the best detection performance. Finally, the pH value of the electrolyte was optimized.

[0088] The sensor has the best detection performance when the pH is 7.4.

[0089] Example 12: Analytical performance of electrochemical sensor for detecting H2O2

[0090] Under the optimal experimental conditions, the prepared immunosensor was used to detect different concentrations of H2O2. Different concentrations of H2O2 were added to 0.1M PBS and used as the electrolyte for the electrochemical sensor DPV measurement. The concentration of H2O2 was 10nM-8mM. Fig.15 A shows the DPV response curve of the present invention under different H2O2 concentration conditions. As the H2O2 concentration gradually increases, the DPV peak current also increases. Fig.15 B shows a good linear relationship between DPV peak current and H2O2 concentration (R2 = 0.9933), and the fitted linear equation is I = 33.6735 + 0.0071C H2O2(μM). The linear range is 0.1-8000μM, and the limit of detection (LOD) is 0.1μM. In addition, compared with the previously reported H2O2 detection method (Table 2), the prepared biosensor has higher sensitivity and wider linear range, which is mainly due to the good oxidase-like activity of Pd-PdCoB MNPs and the excellent conductivity of DDA-Cu MOFs.

[0091] Table 2 Comparison of methods for detecting H2O2

[0092]

[0093] Example 13: Specificity, repeatability and stability of electrochemical sensors

[0094] Under the optimal experimental conditions, the specificity, repeatability and stability of the electrochemical sensor were evaluated. Fig.15 As shown in A, 0.1M PBS was used as the electrolyte, and 1mg / ml glucose, citric acid, uric acid, ascorbic acid, and urea were added thereto respectively. The DPV detection was performed using an electrochemical workstation, and its size was comparable to that of the blank control. When 3mM was added to the electrolyte, the DPV peak current increased significantly, indicating that the electrochemical sensor has excellent detection specificity.

[0095] 0.1M PBS containing H2O2 was used as the electrolyte. The concentration of H2O2 was set to 6mM, 3mM, and 1mM. The peak value of DPV current was measured using an electrochemical workstation and repeated 10 times to evaluate its repeatability. Fig.15 As shown in B, the electrochemical sensor has good repeatability.

[0096] Using 0.1M PBS containing 5mM H2O2 as the electrolyte, the DPV peak was measured 20 times within 200 seconds to evaluate the stability of the electrochemical sensor. Fig.15 As shown in C, the electrochemical sensor has good stability.

[0097] Example 14: Electrochemical sensor for detecting H2O2 in cancer cells

[0098] The cancer cell lines non-small cell lung cancer cells (A549), breast cancer cells (MCF-7), oral epithelial cancer cells (CA922) were cultured as test cells, bronchial epithelial cells (BEAS-2b) were used as normal controls, and blank controls were set up at the same time. 5 mL of high-glucose DMEM complete medium containing 10% fetal bovine serum was added to the culture dish and cultured in a 37°C, 5% CO2 incubator. Before testing the cells, 100 ul of 1 mg / ml ascorbic acid (AA) was placed in the test solution to stimulate the cancer cells to release intracellular H2O2. 1*10 6 When AA was used to stimulate the DPV signal, the DPV signal increased significantly. After the addition of catalase, the DPV signal dropped rapidly. At the same time, the BEAS-2b normal control had no obvious DPV signal, which was the same as the blank control. Fig.17 As shown, this indicates that the sensor can sensitively detect H2O2 released by cancer cells.

Claims

1. A material for enhancing electrochemical detection sensitivity, wherein the material is selected from palladium-palladium cobalt boron single-atom mesoporous nanozyme or / and DDA-Cu electrode modification material, wherein DDA represents 1,5-diamino-4,8-dihydroxy-9,10-anthraquinone.

2. A material for enhancing electrochemical detection sensitivity according to claim 1, characterized in that: The morphology of the palladium-palladium cobalt boron single-atom mesoporous nanozyme is a dendritic monodisperse spherical shape.

3. A material for enhancing electrochemical detection sensitivity according to claim 1, characterized in that: The palladium-palladium cobalt boron single-atom mesoporous nanozyme has excellent peroxidase activity.

4. A material for enhancing electrochemical detection sensitivity according to claim 1, characterized in that: The preparation method of the palladium-palladium cobalt boron single-atom mesoporous nanozyme comprises the following steps: S1. Add NH4F solution, H3BO3 solution, H2PdCl4 solution and Co(NO3)2 solution to the aqueous solution of dioctadecyl dimethyl ammonium chloride in sequence, and after incubation, add NH3·H2O solution and stir to react; S2, heating the solution prepared in S1, injecting the newly prepared borane dimethylamine complex solution, and fully stirring the reaction to obtain PdCoB MNPs; S3. The PdCoB MNPs synthesized in S2 were dissolved in N,N-dimethylformamide, and Na2PdCl4 solution was added. After stirring at low temperature for several hours, the mixture was repeatedly washed with anhydrous ethanol to obtain palladium-palladium cobalt boron single-atom mesoporous nanozymes, named Pd-PdCoB MNPs.

5. A material for enhancing electrochemical detection sensitivity according to claim 4, characterized in that: The mass percentage of the NH3·H2O solution is 12wt.%, the concentration of the borane dimethylamine complex solution is 0.1M, and the concentration of the Na2PdCl4 solution is 10mM.

6. A material for enhancing electrochemical detection sensitivity according to claim 1, characterized in that: The DDA-Cu electrode modification material is an organic metal framework obtained by reacting 1,5-diamino-4,8-dihydroxy-9,10-anthraquinone, copper acetate and anhydrous ethanol, and is named DDA-Cu MOFs.

7. The material for enhancing electrochemical detection sensitivity according to claim 1, characterized in that: The DDA-Cu electrode modified material is a rod-shaped structure.

8. An electrochemical sensor, characterized in that: The electrochemical sensor includes a modified glassy carbon electrode and a signal label on the surface of the modified glassy carbon electrode; the signal label is the palladium-palladium cobalt boron single-atom mesoporous nanozyme described in any one of claims 1 to 7, and the modified glassy carbon electrode is a glassy carbon electrode modified by the DDA-Cu electrode modification material described in any one of claims 1 to 7.

9. A method for constructing an electrochemical sensor according to claim 8, characterized in that The following steps are involved: S1. Preparation of modified glassy carbon electrode: dripping DDA-Cu electrode modification material solution on the surface of the purified glassy carbon electrode, and drying at 37°C to form a film; S2. Add palladium-palladium cobalt boron single-atom mesoporous nanozyme solution dropwise onto the surface of the modified glassy carbon electrode and dry at 37° C. to obtain the electrochemical sensor.

10. An electrochemical sensor according to claim 8 for detecting the H2O2 content in cell supernatant.